2021
DOI: 10.3390/microorganisms9102124
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Environmental Pseudomonas Isolates Reveals Mechanisms of Biodegradation of Naphthenic Acid Fraction Compounds (NAFCs) in Oil Sands Tailings

Abstract: Naphthenic acid fraction compounds (NAFCs) are highly recalcitrant constituents of oil sands tailings. Although some microorganisms in the tailings can individually and synergistically metabolize NAFCs, the biochemical mechanisms that underpin these processes are hitherto unknown. To this end, we isolated two microorganisms, Pseudomonas protegens and Pseudomonas putida, from oils sands tailings and analyzed their transcriptomes to shed light on the metabolic processes employed by them to degrade and detoxify N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A few studies have reported that mixed indigenous microbial communities, rather than a single taxon, are more likely to promote the degradation of recalcitrant compounds due to complementary degradation steps or consumption of intermediate products in syntrophic relationships (communal metabolic efforts). For instance, mixed bacterial communities have been shown to degrade model NAs more rapidly than pure cultures (Demeter et al 2014 ), and Pseudomonas co-cultures degraded a higher quantity of NAs in OSPW than was observed in pure cultures (Chegounian et al 2021 ). Similarly, co-cultures of algae and microorganisms in inocula from an end pit lake degraded cyclohexaneacetic acid while the pure algal cultures or pure end pit lake inoculum did not (Yu et al 2019 ).…”
Section: Factors Influencing the Biodegradability Of Nasmentioning
confidence: 99%
“…A few studies have reported that mixed indigenous microbial communities, rather than a single taxon, are more likely to promote the degradation of recalcitrant compounds due to complementary degradation steps or consumption of intermediate products in syntrophic relationships (communal metabolic efforts). For instance, mixed bacterial communities have been shown to degrade model NAs more rapidly than pure cultures (Demeter et al 2014 ), and Pseudomonas co-cultures degraded a higher quantity of NAs in OSPW than was observed in pure cultures (Chegounian et al 2021 ). Similarly, co-cultures of algae and microorganisms in inocula from an end pit lake degraded cyclohexaneacetic acid while the pure algal cultures or pure end pit lake inoculum did not (Yu et al 2019 ).…”
Section: Factors Influencing the Biodegradability Of Nasmentioning
confidence: 99%